Effect of meticulous nursing on incidence of positional plagiocephaly in extremely low birth weight infants (精细化护理对极低出生体质量儿斜头畸形发生率的影响) - ZHANG Ling (张玲); ZONG Jingting (踪静婷); ZHOU Wei (周伟) (中西医结合护理)
Objective To investigate the effect of meticulous nursing on incidence of positional plagiocephaly among extremely low birth weight infants in the neonate intensive care unit (NICU). Methods Sixteen extremely low birth weight infants who were admitted to the NICU between January and June 2019 were included as the control group, another 17 extremely low birth weight infants who were admitted to the NICU between July and December 2019 were recruited in the observation group. The control group received routine care, and the observation group received meticulous nursing on the basis of normal intensive care. The incidence and severity of positional plagiocephaly were compared between the two groups. Results The incidence of positional plagiocephaly in the observation group was lower than that in the control group (P＜0. 01), and positional plagiocephaly was less severity in the observation group than that in the control group (P＜0. 01). Conclusion The meticulous nursing is potentially effective to reduce the incidence and severity of positional plagiocephaly in extremely low birth weight infants. (目的 评估精细化护理在改善极低出生体质量儿斜头畸形发生率与严重程度中的应用效果。方法 选取2019年1月—6月进入新生儿重症监护病房(NICU)并存活的16例极低出生体质量儿为对照组, 选取2019年7月—12月进入NICU并存活的17例极低出生体质量儿为观察组。对照组采用常规护理方法, 观察组实施精细化护理。比较2组患儿斜头畸形的发生率与发生的严重程度。结果 观察组斜头畸形发生率低于对照组, 斜头畸形发生的严重程度较对照组轻, 差异有统计学意义(P＜0. 01)。结论 精细化护理可降低极低出生体质量儿斜头畸形的发生率与发生的严重程度。)